Association between TLR-9 gene rs187084 polymorphism and knee osteoarthritis in a Chinese population. Issue 5 (17th October 2017) - Zheng, Mingfeng; Shi, Shiyuan; Zheng, Qi; Wang, Yifan; Ying, Xiaozhang; Jin, Yanghui
Abstract : Osteoarthritis (OA) is a complex disease that is induced by many genetic risk variants and other factors. To examine the role of toll-like receptor 9 (TLR-9) in OA patients, we conducted a case–control study involving 215 knee OA (KOA) patients and 215 controls in a Chinese population. Genotyping with a custom-by-design 48-Plex single nucleotide polymorphism Scan™ Kit showed the TLR -9 gene rs187084 polymorphism was associated with an increased risk of KOA. Stratification analyses further validated this finding among old people (age ≥ 55 years). In conclusion, TLR -9 gene rs187084 polymorphism is positively correlated with susceptibility to KOA, especially among old people. Nevertheless, this finding should be confirmed by larger size studies with more ethnic populations.